SIMBOLISASI TRADISI NGABDUL QODIRAN DI PONDOK PESANTREN AL LUQMANIYYAH YOGYAKARTA: Kajian Living Qur’an - Qohar Al Basir (Diya Al-Afkar: Jurnal Studi al-Quran dan al-Hadis, 2019)
There are many symbols that the writer found in Ngabdul Qodiran tradition which are not found in manaqiban and Shaykh 'Abdul Qodir al-Jailani's haul traditions, which all are the same practices in which their activities use the Wasilah to Shaykh' Abdul Qodir al -Jailani. There are a number of texts that distinguish them one to the others. In manaqiban, the texts read are the history of Shaykh 'Abdul Qodir which were written in the form of a story and syi'ir. In haul, the texts read are Surah Yasin and tahlil texts which are directly sent to the deceased. While in Ngabdul Qodiran tradition, the texts read are selected surahs and dzkir as asmaul husna. In addition, special dishes of Ngabdul Qodiran are inseparable in the series of Ngoddul Qodiran tradition; all of which have their own meanings and contain great wishes. In the phenomenon of Ngabdul Qodiran tradition, it is found that there are symbols which have their respective purposes.